Synthesized biopetrol from rubber seeds: heterogeneous catalytic cracking by granular copper - Wan Nur Salwani, Wan Jusoh (2010)
Biopetrol is the alternative process to produce petrol. Biopetrol has the same characteristic in terms of molecular formula with commercial petrol. Biopetrol is environmental friendly because the process using agriculture oil as raw material.The objectives of this research are to synthesize isooctane from fatty acid extracted from rubber seed, to analyze the concentration of isooctane through gas chromatography and to increase the concentration yield of biopetrol through heterogeneous catalytic cracking method. Fatty acid can produce the isooctane through catalytic cracking by using transition metals as catalyst. Rubber Seeds (Kernels) in good condition were cleaned, shelled, ground and dried at 105°C for 30 min. Extraction of fatty acid from rubber seed using soxhlet extraction method. Later, remove the solvent by rotary evaporator. The 20g of granular copper and granular bumping are mix with fatty acid during the catalytic cracking process. Heat is supplied using hot plate at 98oC about 2 hour. Preparation Standard Calibration Curve for standard Isooctane solution. Gas chromatography is used for the qualitative and quantitative analysis of the samples. The isooctane obtained is around in fatty acid with granular copper. Backward calculation is applied to calculate the actual concentration of isooctane in the fatty acid.The gas chromatography result showed that, the actual iso-octane concentration is about 82.7% until 98.2%. The result show higher than the expected result because of the factor of random reaction in catalytic cracking process, the small quantity of analysis, rubber seed contain rich fatty acid had been converted to shorter isooctane chain.